Concept of a miniature photonic spatial switch based on an off-axis zone plate. (August 2021) - Geints, Yu E; Minin, O V; Minin, I V
Abstract: A new concept of an all-optical wavelength-selective twochannel switch based on the photonic hook effect without the use of micromechanical devices or nonlinear materials is proposed. A prototype of such a device based on an off-axis Fresnel zone plate is considered and its main parameters are discussed. Due to the unique property of the photonic hook to change its curvature with respect to the irradiation wavelength l, this switch is a promising candidate for the implementation of optical switching in modern optoelectronics and miniature 'on-a-chip' devices. Numerical simulation shows that the optical isolation of switched channels for a switch with linear dimensions of about (6λ) 3 based on an off-axis zone plate can reach 18–20 dB during operation in the wavelength range of 1.5–1.9 μm.